انعكاس الأزمة على أرقام العجز في الموازنة العامة في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تعتبر مشكلة العجز في الموازنة العامة في سورية من المشاكل القديمة في موضوع مالية الدولة، ولكن مع بداية الأزمة ازداد حجم هذا العجز كنتيجة لانخفاض حصيلة الواردات وزيادة النفقات العامة، فأصبح  ينظر إليه على أنه من المشاكل التي تؤزم من الوضع الراهن، حتى أن البعض تحدث عن أن حالات التضخم التي عانى منها الاقتصاد السوري جاءت نتيجة هذا العجز وتمويله بالإصدار النقدي الجديد، ومن هنا يناقش هذا البحث موضوع عجز الموازنة، حيث تم بدايةً دراسة أهم المفاهيم المتعلقة بالموازنة العامة والعجز وأسبابه وأنواعه وكيفية نظر المدارس الاقتصادية المختلفة لهذا الموضوع وذلك في جزئه الأول، بينما ناقش الجزء الثاني واقع الموازنة العامة في سورية، وأهم أسباب ارتفاع أرقام العجز خلال الفترة الماضية، كما تطرق إلى التطورات التي حصلت على جانبي الموازنة (الإيرادات العامة والنفقات العامة)، وفي النهاية تم تقديم أهم المقترحات التي من شأنها إيجاد السبل للخروج من هذه المشكلة. The problem of Budget Deficit in Syria is one of the old problems in the subject of state finances. However, with the beginning of the crisis, the size of this deficit increased as a result of the decrease in the proceed of revenues and the increase in public expenditure, which was considered to be a problem of the current situation. Even someone talked That the inflation in the Syrian economy came as a result of this deficit and funding it by new coin, and this study discusses the subject of budget deficit, where it was the beginning of the study of the most important concepts related to the general budget and deficit and its causes and types and how different economic schools look at  it and that at the first part of this study, while the second part discussed the reality of the general budget in Syria, and the main reasons for the high deficit figures during the last period. also touched on the developments that took place on both sides of the budget (public revenues and public expenditure). Finally, present propositions to logout of this problem